2019
DOI: 10.1186/s12893-019-0637-y
|View full text |Cite
|
Sign up to set email alerts
|

Major lower extremity amputation: a contemporary analysis from an academic tertiary referral centre in a developing community

Abstract: BackgroundWe aimed to explore the surgical outcomes of major lower extremity amputation (MLEA) and influencing factors at an academic tertiary referral centre in north Jordan, optimistically providing a platform for future health care policies and initiatives to improve the outcomes of MLEA in Jordan.MethodsClinical records of patients who had undergone MLEA between January 2012 and December 2017 were identified and retrospectively reviewed. International Classification of Diseases codes were used to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 38 publications
6
20
1
3
Order By: Relevance
“…In line with other studies, 87.3% of individuals in our cohort had a PVD and were older (73.6 versus 69.0 years, p < 0.001) with a signi cantly higher burden of comorbidities such as renal disease (40.6% versus 23.7%, p < 0.001), CHF (31.1% versus 13.1%, p < 0.001), stroke (28.9% versus 15.0%, p < 0.001), and the mean ACCI score (6.3 versus 4.1, p < 0.001) than those without PVD. In agreement with our results, a study found a high proportion of ischemic heart disease (46.0%), CHF (31.6%), stroke (27.7%), and chronic kidney disease (25.0%) among patients with arteriopathy [27]. Research has also shown a strong association between the accumulating burden of comorbidities and the risk of LEA.…”
Section: Discussionsupporting
confidence: 92%
“…In line with other studies, 87.3% of individuals in our cohort had a PVD and were older (73.6 versus 69.0 years, p < 0.001) with a signi cantly higher burden of comorbidities such as renal disease (40.6% versus 23.7%, p < 0.001), CHF (31.1% versus 13.1%, p < 0.001), stroke (28.9% versus 15.0%, p < 0.001), and the mean ACCI score (6.3 versus 4.1, p < 0.001) than those without PVD. In agreement with our results, a study found a high proportion of ischemic heart disease (46.0%), CHF (31.6%), stroke (27.7%), and chronic kidney disease (25.0%) among patients with arteriopathy [27]. Research has also shown a strong association between the accumulating burden of comorbidities and the risk of LEA.…”
Section: Discussionsupporting
confidence: 92%
“…Year after year, many studies have reported consistently high mortality rates after mELAs, notwithstanding a more aggressive policy toward peripheral revascularization, better medical management, and preoperative optimization, in addition to anesthetic improvements [2,[17][18][19]. In our experience, early mortality remained unchanged for the past decade and is consistent with the 7.6-22.5% reported in several real-world experiences, not falling below 14% in the four quartiles of the period of study (Table 6) [3,[5][6][7][17][18][19][20][21][22][23][24][25][26][27]. Our results are similar to Jones et al [3], who analyzed 186,338 older patients with identified PAOD who underwent mLEA, namely the largest cohort published up to date.…”
Section: Discussionsupporting
confidence: 88%
“…However, while prior investigators have reported that an increased perioperative mortality rate in AKA patients was associated with the presence of advanced ischemia, the most determining factor for AKA in our experience was older age [5,19]. On one hand, it further underlines the impact of age on mLEA outcomes as BKA patients had a higher incidence of diabetes, chronic kidney disease, or hemodialysis [17,26,30,31]. The association of these comorbidities with BKA is the main rationale as to why a BKA was significantly associated with postoperative complications, and more frequently required proximal revision surgery because of stump failure [17].…”
Section: Discussionmentioning
confidence: 67%
“…Whether or not various risk factors are associated with increased mortality and morbidity rates after LLA remains to be elucidated because there is no consensus on this in the literature. [31,32] In our study, amputees with pre-existing infections and renal, neurological, respiratory, cardiac, vascular, endocrine, and gastrointestinal disorders were significantly associated with higher 30-day mortality and rate of complications. Moreover, patients with continuous tobacco smoking habits, a major level of amputation, and PVD or trauma as the primary indication for surgery had higher rates of complications and consequently worse outcomes; this finding is in line with published studies.…”
Section: Discussionmentioning
confidence: 53%